Citra Bapak Rumah Tangga dalam Perubahan Nilai dan Keluarga pada Film “I Am Sam” - Rizki Nurcahya; Tresia Robela Yeni; Antiana Nantri; Dahniar TH Musa; Annisa Rizqa Alamri (Jurnal Hawa : Studi Pengarus Utamaan Gender dan Anak, 2023)
The family is the first place where children learn to be socially oriented, children begin to learn how to respond to the society and adapt in the midst of a wider social life later. The family environment is the main and first growing education center that can influence the development of children both in terms of character, and way of thinking. This research is taken from the movie "I Am Sam", which tells about the struggle of a father who raises his son, even though he has a disability. There are changes in the values contained in this movie. The method used in this research is descriptive method. Primary data in this research is contained in the movie "I Am Sam", and secondary data is obtained through literature study of several previous articles that discuss gender issues in films and gender anthropology. The literature study method is a research method carried out by studying written works or literature related to the topic under study. The result of the discussion and analysis is the representation of the image as a father who can nurture and not hesitate to show demonstrating affection to children and family.